(untitled) (Western European Journal of Medicine and Medical Science, 2026)
Glutathione S-transferases (GSTs) are phase II detoxification enzymes involved in the metabolism of xenobiotics and protection against oxidative stress. The null genotypes of GSTM1 and GSTT1 genes result in complete absence of enzymatic activity, potentially increasing susceptibility to liver damage during viral hepatitis infections. This study aimed to determine the frequency of GSTM1 and GSTT1 null genotypes in patients infected with hepatitis B virus (HBV) and hepatitis C virus (HCV) using real-time PCR. Blood samples were collected from 60 patients (30 HBV, 30 HCV). Genomic DNA was extracted, and GSTM1/GSTT1 genotypes were determined using TaqMan real-time PCR assays. The GSTM1 null genotype was observed in 40% of HBV patients and 46.7% of HCV patients, while GSTT1 null genotype was present in 33.3% and 36.7% of HBV and HCV patients, respectively. Combined null genotypes (GSTM1/GSTT1) were found in 13.3% of HBV and 16.7% of HCV patients. These findings suggest that null genotypes are relatively common among hepatitis patients and may be associated with increased vulnerability to oxidative liver injury. Identification of GSTM1 and GSTT1 genotypes could inform personalized approaches for monitoring and managing viral hepatitis patients